A case of recurrent epiphrenic esophageal diverticulum treated with lower esophagogastric resection and interstitial jejunal reconstruction. Issue 4 (12th April 2023) - Ito, Ayaka; Kitazono, Masaki; Fujita, Makoto; Ikeda, Naotaka; Eguchi, Mayumi; Oyama, Tomohiro; Uchiyama, Shuichiro; Toyosaki, Ryoichi; Suenaga, Toyokuni
Abstract: The patient is a 60-year-old female with a history of multiple times of recurrences of an esophageal diverticulum. She was referred for a diagnosis of persistent dysphagia and vomiting. Balloon dilation did not improve the symptoms; thus, she was referred for surgery. Esophageal fluoroscopy revealed a 5 cm diverticulum. There was no significant change in the size before and after dilation. Gastrointestinal endoscopy revealed a diverticulum in the lower esophagus, with a residue accumulation. The esophagus directly below the diverticulum was narrowed. The patient was diagnosed with recurrent lower esophageal diverticulum and underwent surgery. The operative findings showed poor coloration of the gastric fundus surrounding operated before by Nissen's method, so the patient underwent lower esophagogastric resection and interstitial jejunal reconstruction. The postoperative course was uneventful and discharged on the 19th day. She is 6 years postoperatively and gained six kg compared to her preoperative weight. She has remained in excellent health.